2016
DOI: 10.11604/pamj.2016.25.202.5669
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis: a retrospective study at Jos abattoir, Plateau State, Nigeria

Abstract: IntroductionNigeria has the thirteenth highest burden of human tuberculosis. The current increasing incidence of tuberculosis in humans, particularly in immune-compromised persons, has given interest in the zoonotic importance of Mycobacterium bovis in developing countries like Nigeria. This study determined the prevalence of bovine tuberculosis as a background information for effective control measures in Plateau State in cattle population.MethodsWe reviewed surveillance records on cattle slaughtered and sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…BTB prevalence between 2014 and 2016 was 6.7%. This was similar to previous studies conducted in Nigeria (Ejeh et al, 2014;Okeke et al, 2016), Pakistan (Memon et al, 2018), Sicily, Southern Italy that cattle organs and/or carcass condemnation were associated with hydatidosis, cysticercosis, fasciolosis, and BTB (Mellau et al, 2011;Tembo and Nonga, 2015), though with lower levels of occurrences except fascioliosis when compared with our study. In our study, abattoir data showed that organ condemnations (both partial and total) were based on lesions observed at postmortem by certified veterinarians.…”
Section: ■ Discussionsupporting
confidence: 93%
“…BTB prevalence between 2014 and 2016 was 6.7%. This was similar to previous studies conducted in Nigeria (Ejeh et al, 2014;Okeke et al, 2016), Pakistan (Memon et al, 2018), Sicily, Southern Italy that cattle organs and/or carcass condemnation were associated with hydatidosis, cysticercosis, fasciolosis, and BTB (Mellau et al, 2011;Tembo and Nonga, 2015), though with lower levels of occurrences except fascioliosis when compared with our study. In our study, abattoir data showed that organ condemnations (both partial and total) were based on lesions observed at postmortem by certified veterinarians.…”
Section: ■ Discussionsupporting
confidence: 93%
“…In a study conducted in a slaughterhouse in Nigeria, tuberculosis showed a cyclical behavior (seasonality), with greater occurrence in July and August, differing from the result found in the present study. The authors related this seasonality to stressful factors that occur in this period (off-season) and the increase in the number of religious slaughters (Okeke et al 2016). The absence of seasonal influence on the occurrence of tuberculosis, observed in the present study, can be explained by the variables, such as: incubation period of the microbiological agent and chronic character of the disease.…”
Section: Discussionsupporting
confidence: 44%
“…[20,21,22,31,32,33,34,35,36,37,38,39,40,41,42]; nine reporting on Leptospira spp. [22,26,27,28,43,44,45,46,47]; 13 reporting on Coxiella burnetii [23,24,25,39,40,41,48,49,50,51,52,53,54]; five on Mycobacterium bovis [42,55,56,57,58]; eight on Rickettsia spp. [25,53,54,59,60,61,62,63]; five reporting on Anaplasma spp.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of lesions in lungs was highly associated (OR = 52.3; 95% CI: 16.4–191.8) with positive results for acid-fast bacilli (AFB) test compared to those without lesions. A retrospective study at a Nigerian abattoir was conducted with an average yearly bovine tuberculosis prevalence rate of 9.1% detected [57].…”
Section: Resultsmentioning
confidence: 99%